2012
DOI: 10.5267/j.msl.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A social work study on the effect of emotional intelligence factors on recovering people addicted to drugs

Abstract: Drug addiction has become serious problem in many developing countries. Many young people are addicted to different toxicated materials and, as a result, they cannot contribute to their societies. They lose any employment opportunity, cannot continue their education and lose their healthcare. This paper considers the effect of emotional intelligence (EQ) and the likelihood of recovery among addicted people who were under recovery treatments in three different groups in city of Esfahan, Iran including community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In addition, their results indicated that Puerto Rican IDUs who were older had overdosed on drugs in the past year, had been incarcerated in their lifetime. Mosavi et al (2012) performed an investigation on the effect of emotional intelligence factors on recovering people addicted to drugs. They considered the impact of emotional intelligence (EQ) and the likelihood of recovery among addicted people who were under recovery treatments in three various groups in city of Esfahan, Iran including community-based treatment (CT) group, no support addictives (NA) and recovery center.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their results indicated that Puerto Rican IDUs who were older had overdosed on drugs in the past year, had been incarcerated in their lifetime. Mosavi et al (2012) performed an investigation on the effect of emotional intelligence factors on recovering people addicted to drugs. They considered the impact of emotional intelligence (EQ) and the likelihood of recovery among addicted people who were under recovery treatments in three various groups in city of Esfahan, Iran including community-based treatment (CT) group, no support addictives (NA) and recovery center.…”
Section: Introductionmentioning
confidence: 99%